PENGARUH LAMA FERMENTASI PADA PRODUKSI MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) TERHADAP SIFAT FISIK, KIMIA, DAN ORGANOLEPTIK - Ngatemin -; Nurrahman -; Joko Teguh Isworo (Jurnal Pangan dan Gizi, 2013)
Virgin coconut oil Virgin coconut oil (VCO) is obtained from fresh coconuts (non-copra) and processed without high-temperature and chemicals. The purpose of the study was to determine the effect of fermentation VCO to the yield, physical properties (density, refractive index), chemical properties (saponification number, acid number, and the number peroksidan), and organoleptic properties (color, aroma, and viscosity). Materials research is the fruit of the coconut meat Typical types (Cocos nucefera lin). The study design used a completely randomized design with duration of fermentation 14, 16, 18, 20, 22, and 24 hours with 4 replications. The results showed no effect on the fermentation yield and physical properties of VCO that includes specific gravity and refractive index, but significantly affect the chemical properties including acid number, saponification and peroxide. Hedonic test the VCO, long fermentation affect the color and viscosity, but does not affect the scent. The yield of the highest VCO in 24-hour fermentation period which is 22%, the highest density in the fermentation of 22 hours is 0.910 g / cm 3 and the highest refractive index of 0.1515 at 24 hours of fermentation. Saponification high of 27.65 mg KOH / g, the lowest value acid value 0.567 mg KOH / g, and the lowest peroxide 1,120 meq / kg at 16 hours of fermentation. A panelist on the level of the highest color 3.3 24 hour fermentation, the aroma of 3.0 A levels at 22 hours of fermentation and viscosity of 2.95 in 16-hour fermentation period.